Ocular surface disorders associated with the use of dupilumab based on WHO VigiBase - Sunny Park (Nature Portfolio, 2021)
Abstract Dupilumab is a dual inhibitor of interleukin-4 and interleukin-13 and is mainly used to treat moderate-to-severe atopic dermatitis. Post-marketing safety data related to dupilumab have been accumulated, and it has been found that ocular surface diseases are closely associated with dupilumab treatment. The aim of this study was to detect dupilumab-related signals and to determine the safety characteristics of dupilumab with respect to eye disorders using real-world big data. Data on dupilumab use until December 29, 2019 were collected. The data were mined by calculating three indices: proportional reporting ratios, reporting odds ratios, and information components. The detected signals were classified using the primary system organ class in MedDRA terminology. Among 21,161,249 reports for all drugs, 20,548 reports were recorded for dupilumab. A total of 246 signals in the preferred terms were detected for dupilumab. Among the 246 positive signals obtained, 61 signals were related to eye disorders, which accounted for the largest percentage (24.8%), and 38 signals were anatomically related to the ocular surface. Dupilumab may cause extensive eye disorders; however, the underlying mechanisms and risk factors remain unclear. Our findings may facilitate broad safety screening of dupilumab-related eye disorders using real-world big data.